PENERAPAN UNDANG-UNDANG NOMOR 1 TAHUN 1970 TENTANG KESELAMATAN DAN KESEHATAN KERJA (K3) BAGI TENAGA KERJA DI INDONESIA - Samud, Samud; Ahmad, Jamhuri (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2020)
Currently, industrial development in Indonesia is growing rapidly so that Indonesia has many different types of industries. The industry in managing its activities uses various levels of technology ranging from simple technology to advanced technology. The higher the technology used, the higher the risk of hazards faced. Indonesia is currently facing many very complex manpower problems. The cumulative number of unemployed continues to increase sharply, in line with the increasing number of school graduates. The problem of unemployment must be addressed immediately so as not to increase the number of unemployed in Indonesia. Various efforts have been made by the government to solve this problem, one of which is by increasing the quality of its human resources so that the quality of the workforce in Indonesia will increase, and not be inferior to the quality of foreign workers. Increasing the quality of Indonesia's workforce, providing opportunities to find jobs, both at home and abroad, are increasingly wide open, thereby reducing unemployment. Keywords: Law Number 1 Year 1970, Occupational Health and Safety (K3), and Labor.